Degradation of aqueous recalcitrant compounds by Sulfate radical based advanced oxidation process - Chau, Yuan Ming (2015)
Bisphenol A(BPA) is known for its adverse health effects of resulting disorder in human immune system and reproductive system. Despite the assorted proposal of BPA treatment techniques, the limitations of these applications such as the leaching of toxic ions and long reaction time hinder them from being the ideal solution BPA removal process. This study intends to develop a novel heterogeneous catalyst which is capable of decomposing BPA via sulfate radical-based oxidation through triggering peroxymonosulfate(PMS) activation, Three novel heterogeneous Copper-Metal Spinel Oxide catalysts(CuM2O4, M=Al, Bi, Fe) were prepared by sol-gel technique and low temperature co-precipitation method. These catalysts were employed to trigger peroxymonosulfate(PMS) activation and generate free, powerful radicals for degrading Bisphenol A(BPA) in water. The XRD, SEM and FTIR characterization pointed out that CuFe2O4 exhibited itself as the best candidate in term of catalyzing the PMS oxidation rate of BPA. The ascending order of the sequence of catalyst’s reducibility is CuAl2O4 < CuBi2O4 < CuFe2O4.The dependency of the catalytic process on initial pH is revealed in this study, mainly due to the protonation of the peroxide bond in PMS under acidic condition. Moreover, sulfate radicals and hydroxyl radicals were defined as the reactive radical species in PMS/CuM2O4. CuFe2O4/PMS system was optimized by varying oxone dosage and catalytic loading. It was found out that catalytic loading was the dominant factor of the PMS activation rate, signifying the importance of the available effective surface area for the radicals generation to be occurred.